Towards Sustainable Practices: Green Accounting Implementation and Reporting Model in a Water Supply Utility: Menuju Praktik Berkelanjutan: Implementasi Akuntansi Hijau dan Model Pelaporan di Perusahaan Daerah Air Minum - Resi Intan Penatari; Terrensia Sekar Pamastutiningtyas; Rauhulloh Ayatulloh Khomeini Noor Bintang (Academia Open, 2023)
This study presents a comprehensive analysis of the implementation of green accounting in a local water supply utility (PDAM) and introduces a green accounting-based reporting model. The research aims to assess the internal and external perspectives of green accounting adoption within PDAM Sukoharjo, employing a descriptive qualitative method. Findings indicate that PDAM Sukoharjo has not fully embraced the green accounting concept. However, this study contributes by introducing a reporting model founded on green accounting principles, promising to enhance stakeholder satisfaction and promote sustainable practices in the water supply sector. Highlight: The study assesses the implementation of green accounting in a local water supply utility, offering insights into its adoption within the sector. Findings reveal that PDAM Sukoharjo has room for improvement in fully embracing the green accounting concept for sustainable practices. The research introduces a novel green accounting-based reporting model aimed at enhancing stakeholder satisfaction and promoting sustainability in the water supply industry. Keyword: Green Accounting, Water Supply Utility, Sustainability, Reporting Model, Stakeholder Satisfaction